Clinical Improvement of Chronic Spinal Cord Injury and Immune Thrombocytopenia (ITP) with Corticosteroids Administration: A Case Report - Talaway, Athalia Anastasia; Machin, Abdulloh; Kurniawan, Dedy (Universitas Airlangga, 2025)
Highlight: Understanding the causes and associated factors of of spinal cord injury (SCI) is important. Immune thrombocytopenia may contribute to spinal cord injury. Corticosteroid therapy for ITP, has shown improved clinical outcomes. ABSTRACT Introduction: Spinal cord injury (SCI) is a significant medical condition caused by either traumatic events or pathological diseases, which leads to neurological deficits and various levels of motor, sensory, and autonomic dysfunction. Several treatments, including corticosteroids, have been proposed to reduce secondary neuronal damage, but they are still controversial. Meanwhile, immune thrombocytopenia (ITP) can be treated with corticosteroids. The lack of research necessitates a review of steroids as a therapy for ITP and spinal cord trauma. Case: A 76-year-old woman complained of weakness in both legs for 15 days before being admitted to the hospital.The weakness was noticed after experiencing a fall. Additionally, the patient complained about having difficulty with both defecating and urinating. On examination, muscle strength in the lower limbs was graded 4 on both sides according to the Medical Research Council (MRC) scale. The classification of the American Spinal Injury Association (ASIA) score was D, with neurological level injury (NLI) at the 6th thoracic level with immune thrombocytopenia (ITP). Considering the patient's condition, steroids were administered as a treatment option. Fortunately, the patient showed clinical improvements, with the ASIA score improving from D to E, suggesting a positive response to steroids and potential for neurological recovery. Conclusion: Steroids may be regarded as a possible treatment alternative for individuals suffering from spinal cord injuries and immune thrombocytopenic purpura (ITP).